Effects of decentralization on school resources - Åsa Ahlin; Eva Mörk (Institute for Labour Market Policy Evaluation (IFAU), 2005)
Sweden has undertaken major national reforms of its schooling sector which, consequently, has been classified as one of the most decentralized ones in the OECD. This paper investigates the extent to which local tax base, grants, preferences and structural characteristics affected local schooling resources as decentralization took place. We use municipal data for the period 1989–95 which covers the key reform years without confounding decentralization with institutional changes after 1995. The main arguments against decentralization are not supported by our findings. First, school spending as well as teacher density is found to be more equally distributed across municipalities following decentralization. Second, local tax capacity does not influence schooling resources more in the decentralized regime than in the centralized regime. We also find that the form in which grants are distributed matter: Targeted grants have a significant positive impact on resources while general grants have not.
Keywords: H40; H52; H70; 330; School resources; school finance reform; decentralization; Schulpolitik; Schulfinanzierung; Bildungsreform; Dezentralisierung; Schweden